2009
DOI: 10.1523/jneurosci.3355-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of DISC1 in Psychiatric Disease and during Normal Development

Abstract: The biology of schizophrenia is complex with multiple hypotheses (dopamine, glutamate, neurodevelopmental) well supported to underlie the disease.Pathwayscenteredontheriskfactor"disruptedinschizophrenia1"(DISC1)maybeabletoexplainandunitethesedisparatehypotheses and will be the topic of this mini-symposium preview. Nearly a decade after its original identification at the center of a translocation breakpoint in a large Scottish family that was associated with major psychiatric disease, we are starting to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 52 publications
3
140
0
2
Order By: Relevance
“…It is interesting to note that while stabilized b-catenin expression can compensate for the effect of Aspm knockdown on deficits in neurogenesis at this stage, no such compensation is observed in terms of neuronal migration. This is consistent with previous observations that knockdown of positive regulators of Wnt signaling impinges on both neurogenesis and neuronal migration, but that only deficits in neurogenesis can be rescued via increased Wntmediated activity (Brandon et al 2009;Mao et al 2009). …”
Section: Expression Of Stabilized B-catenin Rescues Defects In Wnt Sisupporting
confidence: 93%
“…It is interesting to note that while stabilized b-catenin expression can compensate for the effect of Aspm knockdown on deficits in neurogenesis at this stage, no such compensation is observed in terms of neuronal migration. This is consistent with previous observations that knockdown of positive regulators of Wnt signaling impinges on both neurogenesis and neuronal migration, but that only deficits in neurogenesis can be rescued via increased Wntmediated activity (Brandon et al 2009;Mao et al 2009). …”
Section: Expression Of Stabilized B-catenin Rescues Defects In Wnt Sisupporting
confidence: 93%
“…The molecular interactions of both DISC1 and 14-3-3Δ are numerous, yet both proteins have been reproducibly implicated in the processes regulating neurite outgrowth and spine density (26,31,33,36,37). 14-3-3Δ binds phosphorylated NDEL1 and serves as a positive regulator of NDEL1 function (37), and active NDEL1 is required for neurite outgrowth (38).…”
Section: Discussionmentioning
confidence: 99%
“…DISC1 is a scaffolding protein that is thought to coordinate other synaptic proteins (30)(31)(32), and indeed plays a key role in synaptic spine maintenance in association with the activation of NMDA receptors (33). Thus, we hypothesized that the results from the unbiased approach might reflect a possible defect of a molecular pathway involving DISC1 in the synapse.…”
Section: Nmda Receptor Deficient Mice Show An Age-dependent Deficit Inmentioning
confidence: 99%
“…The biological functions attributed to the DISC1 protein are complex and highly diverse. For example, previous work suggested that DISC1 plays an important role during neuronal proliferation, differentiation, neurite outgrowth, synapse formation, as well as in the genesis and integration of new neurons in the adult hippocampus (for review, see Brandon et al, 2009). There are also several studies that report that DISC1 is a necessary component for the correct positioning of radially migrating cortical pyramidal neurons (Kamiya et al, 2005;YoungPearse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%